Anatomy and origin of large scale foreset beds in the Capitan Formation, Glass Mountain, Texas - Haneef, Mohammad; Rohr, D.M. (Journal of Himalayan Earth Sciences, 1995)
Large scale foresetbeds occur in the Capitan Formation of the Glass Mountains, west Texas. These beds are clinoforms of basinward dipping, massive, partially to completely dolomitized beds that interfinger with slope and basinal facies of the time-equivalent Altuda Formation. The foreset beds represent deposition of reef and backreef derived, allochthonous sediments shed off of the Capitan shelf-edge in shelf-to-basin slope transition. On the basis of lithology, texture and bedforms, various subaqueous gravity flow processes are recognized, including debris flow, grain flow and submarine slide and slump blocks. High energy conditions along with sea level fluctuations on the Capitan shelf-edge produced carbonate debris that moved under the influence of gravity and were deposited on the foreslope as multiple debris sheets.